Rancang Bangun Jig and Fixture untuk Proses Machining Balance Weight pada Mesin CNC Milling 3 Axis - Indah Alviana Putri; Pranowo Sidi; Geroge Endri Kusuma (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Companies engaged in manufacturing one of them is CV Gaya Indah which has produced a variety of component products for industrial needs. Balance weight is one of the products in production, in the manufacture of this product there are several plans to produce quality product. In the manufacture of balance weight products there is a difficult drill position to machining and requires mass production. This machining process requires supporting tools namely jig and fixture. Jig and fixture are needed to speed up the machining time of balance weight products accurately according to standards. The stages of designing a jig and fixture include a list of requirements, product dimensions, and knowing the characteristics of the machine used for its production. This research uses the Ulrich method which made three design concepts with two types of jigs, namely jig drilling and jig milling. Calculation stage in selection of bolts to ensure the bolts can withstand the Balance Weight on the jig and fixture well. The results of analysis and design of jig and fixture balance weight for machining process on CNC Milling 3 Axis machine, produce the product within 18 minutes with testing that produces acceptable products according to standards.